Advances in Privacy Preservation Techniques for Mobile Ad Hoc Networks: A Review - Opeyemi O. ASAOLU; Oluwasanmi S. ADANIGBO; Temidayo J. AKINDAHUNSI (FUDMA Journal of Engineering and Technology, 2026)
This literature review examines recent developments in privacy preservation techniques for Mobile Ad Hoc Networks (MANETs) through a systematic analysis of 49 peer-reviewed journal articles published between 2020 and 2025. The review focuses on four principal technical domains: blockchain-based privacy frameworks, advanced homomorphic encryption implementations, differential privacy mechanisms, and federated learning applications in mobile networks. It further addresses the convergence of these techniques with Internet of Things (IoT) and edge computing paradigms. The analysis reveals significant evolution in privacy preservation methodologies, with a discernible trend toward context-aware privacy mechanisms, lightweight cryptographic solutions tailored to resource-constrained environments, and hybrid approaches that integrate complementary techniques to achieve comprehensive protection. The review identifies the absence of standardised benchmarks, unresolved tensions between privacy and accountability, and the scarcity of real-world deployment studies as the most critical open challenges facing the field. The findings demonstrate substantial progress in addressing classical MANET privacy challenges while highlighting the novel demands introduced by contemporary mobile network applications, including vehicular networks, smart city infrastructure, and autonomous systems.
Keywords: Mobile Ad Hoc Networks, Privacy Preservation, Homomorphic Encryption, Differential Privacy, Federated Learning.